IGM transmission bias for z ≥ 2.9 Lyman continuum detected galaxies. Issue 1 (13th January 2021) - Bassett, R; Ryan-Weber, E V; Cooke, J; Meštrić, U; Kakiichi, K; Prichard, L; Rafelski, M
ABSTRACT: Understanding the relationship between the underlying escape fraction of Lyman continuum (LyC) photons ( f esc ) emitted by galaxies and measuring the distribution of observed f esc values at high redshift is fundamental to the interpretation of the reionization process. In this paper, we perform a statistical exploration of the attenuation of LyC photons by neutral hydrogen in the intergalactic medium using ensembles of simulated transmission functions. We show that LyC-detected galaxies are more likely to be found in sightlines with higher than average transmission of LyC photons. This means that adopting a mean transmission at a given redshift leads to an overestimate of the true f esc for LyC-detected galaxies. We note, however, that mean values are appropriate for f esc estimates of larger parent samples that include LyC non-detected galaxies. We quantify this IGM transmission bias for LyC detections in photometric and spectroscopic surveys in the literature and show that the bias is stronger for both shallower observations and for fainter parent samples (i.e. Ly α emitters versus Lyman break galaxies). We also explore the effects of varying the underlying probability distribution function (PDF) of f esc on recovered values, showing that the underlying f esc PDF may depend on sample selection by comparing with observational surveys. This work represents a first step in improved interpretation of LyC detections in the context of understanding f esc from high-redshift galaxies.